Grouping tau topologies in former boxers assessed by PET with 18F‐PM‐PBB3: A reappraisal of dementia pugilistica: Neuroimaging / Optimal neuroimaging measures for tracking disease progression. (7th December 2020) - Takahata, Keisuke; Shimada, Hitoshi; Kubota, Manabu; Seki, Chie; Tagai, Kenji; Matsuoka, Kiwamu; Miyata, Mari; Sano, Yasunori; Yamamoto, Yasuharu; Saito, Fumie; Mizushima, Jin; Anamizu, Sachiko; et al.
Abstract: Background: Accumulation of hyperphosphorylated tau is a core feature of late‐life sequalae of mild‐repetitive traumatic brain injury (mrTBI). Brain‐bank surveys have demonstrated that chronic traumatic encephalopathy (CTE), defined as tau accumulation at the depths of cortical sulci, is a typical neurodegenerative condition associated with mrTBI exposure. In contrast, early case‐reports of dementia pugilistica (DP) in former boxers described considerable heterogeneity of late‐life neurodegenerative changes. Despite such inconsistency, topology of tau accumulation in the living brain of mrTBI patients have not been fully investigated. The present study was aimed to characterize cerebral retention patterns of 118 F‐PM‐PBB3 ( 18 F‐APN‐1607) in the former boxers. Method: Thirteen former boxers (46.2 ± 11.9 years) and 15 age‐matched healthy control (HC) subjects underwent PET scans with 18 F‐PM‐PBB3 and [ 11 C]PiB. Standard uptake value ratio (SUVR) with the cerebellar gray matter as reference was calculated. Association of SUVR with neurocognitive symptoms and years of playing boxing was investigated. Result: All subjects were [ 11 C]PiB negative. Boxers showed higher 18 F‐PM‐PBB3 accumulation than HC subjects in the gray ( P = 0.0002) and white matter ( P = 0.0001). There was a trend of correlation between SUVR values in the temporal cortex and years of exposure to concussions ( p =0.07, r =0.40). Visual assessments revealed heterogeneity in 18 F‐PM‐PBB3 retention patterns in boxers. First, the majority of boxers (7/13) demonstrated multiple 18 F‐PM‐PBB3 accumulations around the depth of cerebral sulci, showing striking resemblance to previously reported tau topology of CTE. Subjects in this group tend to show severe memory impairment and depression. Second, a few boxers (3/13) showed diffuse 18 F‐PM‐PBB3 accumulation, indicating some form of non‐AD tauopathy but currently unspecified. Subject in this group showed psychiatric symptoms such as psychosis and mania. Third, the other 3 boxers showed minimum 18 F‐PM‐PBB3 retention regardless of clinical symptoms. Conclusion: Our results indicates different forms of tau neuropathology underlying late‐sequalae of mrTBI in agreement with the classical concept of DP. These forms vary in where and how much tau accumulate, as well as in clinical features. The present study not only supports pathological heterogeneity of late‐sequalae of mrTBI, but also suggests utility of 18 F‐PM‐PBB3 PET in detection of late‐life neurodegenerative diseases following mrTBI.